China's macroeconomic imbalances: Causes and consequences. - Knight, J; Wang, W (Blackwell Publishing, 2011)
In recent years, China has experienced two forms of extreme macroeconomic imbalance: an expenditure imbalance in the sense of very high investment and very low consumption, giving rise to rapid capital accumulation; and an imbalance between expenditure and production, producing external imbalance, i.e. a huge surplus on the current account of the balance of payments. Both imbalances imply a low rate of time discount by both government and society: consumption in the present is forgone in favour of consumption in the future. The paper examines how these imbalances came about and goes on to consider whether they can be sustained and how they might be redressed. There is no evidence that the rapid capital accumulation has reduced the rate of profit on capital and thus the incentive to invest. However, persistent external imbalance poses a threat to investment if it generates excess liquidity and asset bubbles. The current account surplus rose remarkably in the years 2004–07. This was associated with exogenous increases in competiveness and in saving, both attributable to the economic reform policies. On current policies, the surplus is likely to rise again once the world economy recovers from its recession. This poses three sorts of problems, each of which is examined in turn: difficulties for macroeconomic stabilisation policies; risk of capital loss on the foreign exchange holdings; and the threat of retaliation by China’s trading partners. A combination of internal and external policies will be required to redress the imbalance.